Decentralized Trusted Storage of Audio-Video Log Data Based on Blockchain Technology and IPFS - Irawan, Bambang; Trihatmojo, Dandung (Publisher Cv. Inara, 2024)
The development of communication and information technology has affected the world of television broadcasting in Indonesia. With the emergence of a new phenomenon, the convergence of digital media industry. The migration of analogue to digital television broadcasting has impacted various industries related to broadcasting. Especially for the sustainability of the television broadcasting community in the country. Station Tv x is one of the television communities, on the other hand the media industry has challenges in managing storage media consisting of audio and video data that has a large capacity. Audio video logs are needed as information on recording audio video files. Blockchain-based Interplenary File System (IPFS) technology is expected to be one of the alternatives that can be applied in the world of broadcasting, storage media and audio video file data distribution methods, data library security and data flexibility are one of the challenges faced in the television broadcasting industry. The purpose of this research is as an effort to decentralise audio video data in distributed storage media to be more optimal and secure. The results of this research can be used to distribute audio video data files in the data library at tv station x.